2011
DOI: 10.1021/jp2016616
|View full text |Cite
|
Sign up to set email alerts
|

Interpolation of Atomically Thin Hexagonal Boron Nitride and Graphene: Electronic Structure and Thermodynamic Stability in Terms of All-Carbon Conjugated Paths and Aromatic Hexagons

Abstract: Two-dimensional hexagonal composite materials (BN) n (C 2 ) m (n, m = 1, 2, ...), which all are isoelectronic with graphene and hexagonal boron nitride (h-BN), have been studied by density functional theory (DFT) with a focus on the relative energies of different material isomers and their band gaps. The well-established chemical concepts of conjugation and aromaticity were exploited to deduce a rationale for identifying the thermodynamically most stable isomer of the specific composites studied. We find that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
63
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 66 publications
(70 citation statements)
references
References 47 publications
7
63
0
Order By: Relevance
“…17 Similarly, in the BN-doped graphene superlattice, the band gap increases with the increasing size of BN nanodots, but regardless of their shapes. 18 In terms of the conjugation and aromaticity concepts, a recent density functional theory (DFT) calculation confirmed that for a certain stoichiometric (BN) n (C 2 ) m monolayer, several isomers with similarly low relative energies have different band gaps by up to 1.0 eV, 19 and this feature is common for the compounds with different n : m ratios and carbon content. 19 These theoretical results have revealed some interesting features different from the ''mean-field'' pictures, in which the electronic properties of BCN layers would be changed asymptotically with the decreasing of carbon content.…”
Section: Introductionmentioning
confidence: 98%
“…17 Similarly, in the BN-doped graphene superlattice, the band gap increases with the increasing size of BN nanodots, but regardless of their shapes. 18 In terms of the conjugation and aromaticity concepts, a recent density functional theory (DFT) calculation confirmed that for a certain stoichiometric (BN) n (C 2 ) m monolayer, several isomers with similarly low relative energies have different band gaps by up to 1.0 eV, 19 and this feature is common for the compounds with different n : m ratios and carbon content. 19 These theoretical results have revealed some interesting features different from the ''mean-field'' pictures, in which the electronic properties of BCN layers would be changed asymptotically with the decreasing of carbon content.…”
Section: Introductionmentioning
confidence: 98%
“…9 Computational studies support the phase separation of such films into carbon and BN domains, with conjugation and aromaticity as driving forces. 10 In such a film graphene domains and h-BN domains are distributed inhomogeneously to form a disordered superlattice. Although the interface between h-BN and graphene domains contains unfavorable B-C and N-C bonds, such mixed films can nevertheless be realized by exploiting growth kinetics.…”
Section: Introductionmentioning
confidence: 99%
“…1, along with other two-dimensional BCN alloys considered theoretically. 3,[13][14][15][16][17][18][19][20] Here, we use the densityfunctional theory and cluster expansion to establish the theoretical limits of N doping in g-NG, and investigate its stability and electronic properties. We demonstrate that the nitrogen concentration in g-NG can in principle be as high as 33.3%-37.5%, and that most of these structures are metallic.…”
mentioning
confidence: 99%
“…Smaller circles show other two-dimensional BCN systems considered previously. 3,[12][13][14][15][16][17][18][19][20] Mixing energies of the 2D carbon-nitrogen alloy were obtained using the cluster expansion (CE) method. 51 …”
mentioning
confidence: 99%